Parasitism of Greenbugs (Homoptera: Aphididae) by Lysiphlebus testaceipes (Hymenoptera: Braconidae) in Grain Sorghum: Implications for Augmentative Biological Control - Fernandes, Odair A. [UNESP]; Wright, Robert J.; Mayo, Z. B. (My University, 1998)
Field cage studies were conducted to describe the relationship between the percentage of Lysiphlebus testaceipes (Cresson) parasitism (as measured by aphid mummies) and densities of greenbug, Schizaphis graminum Rondani, on grain sorghum, Sorghum bicolor L. In 1993 and 1994, a biotype E-susceptible grain sorghum hybrid was grown in field cages and L. testaceipes adults were released after each plant was infested with 20 biotype E greenbugs. The release rates were 0, 0.5, 1.0, and 2.0 wasps per plant in 1993, and 0, 0.16, 0.33, and 0.5 wasps per plant in 1994. Greenbugs and mummies were counted 1-2 times a week on all leaves of 2-4 randomly selected plants per cage. A release rate of 0.33-0.5 wasps per plant infested with 20 greenbugs maximized the number of mummies produced and prevented the greenbugs from reaching an economic threshold of 1,000 greenbugs per plant. Peak numbers of mummies occurred ≈400-500 DD (10°C base) after the initial wasp release. Regression analyses showed that the greenbug population started decreasing when the percentage of parasitism (as measured by mummies) reached 20-30 %. Greenbugs in the absence of wasps significantly reduced yield in 1994, but not in 1993.
Keywords: Augmentation; Biological control; Grain sorghum; Greenbugs; Parasitoids